La poetessa Siria, autrice del centone Alcesta - PAOLUCCI, Paola (AL. Rivista di studi di Anthologia Latina, 2014)
Abstract In the Late Antiquity, various potesses (the most famous were Proba and Eudocia) wrote Centos. Now we can know another one, the poetesse Siria, who probably wrote the Cento Alcesta. She gave her name in the first seven verses of her Vergilian Cento with the literary device of the acrostichon, looking up to the beginning acrostichon of the Alcestis Barcinonensis and conveying the plentiful epigraphic poetry with acrosticha of African area, illustrated in an appendix of this paper.